THE EFFECT OF TRADITIONAL GAMES (BROKEN CANS) ON EARLY CHILDHOOD HYPERACTIVE BEHAVIOR - Bertyn Mogelea; Elsye Rahmawati; Jamiatun; Septiyani Endang Yunitasari; Yeny Burumi; Zenab Hulukati (International Conferences on Early Childhood Education Proceedings, 2023)
The problem in this study is hyperactive behavior in early childhood so that children cannot adjust to the environment. In this study, researchers used qualitative methods with data collection techniques by means of observation, interviews and documentation. Based on the results of the final observation, HS has shown an increase in behavioral changes in interacting with his friends. HS began to show a positive attitude to want to play with his friends, HS has dared to join his friends to follow the traditional game activities of broken cans even though HS has not played according to the rules of the game. HS began to focus on the teacher's instructions when told to arrange the cans in the shape of a tower even though it did not last long about 3 minutes. HS has been able to control himself to patiently wait for his turn even if only briefly. HS screamed with joy when he successfully kicked the ball into the cans that had been neatly arranged so that it fell apart. But at that time HS was still unable to control his emotions, HS cried hysterically when he fell because he was wrong to kick the ball for a long time.